2022
DOI: 10.3390/polym14010167
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Adsorption of Major Enzymes in a Cellulase Cocktail Obtained from Trichoderma reesei onto Different Types of Lignin

Abstract: Cellulase adsorption onto lignin decreases the productivity of enzymatic hydrolysis of lignocellulosic biomass. Here, adsorption of enzymes onto different types of lignin was investigated, and the five major enzymes—cellobiohydrolases (CBHs), endoglucanase (Cel7B), β-glucosidase (Cel3A), xylanase (XYNIV), and mannanase (Man5A)—in a cellulase cocktail obtained from Trichoderma reesei were individually analyzed through SDS-PAGE and zymogram assay. Lignin was isolated from woody (oak and pine lignin) and herbaceo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 62 publications
(95 reference statements)
0
2
0
Order By: Relevance
“…Notably, the lignin remaining after the pretreatment may contribute to redox side reactions that consume or produce H 2 O 2 , and it may also prevent LPMOs from optimally accessing cellulose. Indeed, it has been shown that the hydrophobic properties of CBM1 (which is present in both Pa AA9E and Pa AA9H) contribute to the nonproductive binding to lignin. , The biomass used in this study indeed contains high concentrations of remaining lignins (Table S3), which could explain the lack of a boosting effect coming from the addition of the tested LPMOs. Therefore, although Pa AA9E and Pa AA9H are efficient cellulolytic AA9s, it appears clearly that observing a high activity on somehow simple cellulosic substrates (such as PASC or Avicel) cannot be taken as a token of efficiency once mixed with cellulases on more complex biomass.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the lignin remaining after the pretreatment may contribute to redox side reactions that consume or produce H 2 O 2 , and it may also prevent LPMOs from optimally accessing cellulose. Indeed, it has been shown that the hydrophobic properties of CBM1 (which is present in both Pa AA9E and Pa AA9H) contribute to the nonproductive binding to lignin. , The biomass used in this study indeed contains high concentrations of remaining lignins (Table S3), which could explain the lack of a boosting effect coming from the addition of the tested LPMOs. Therefore, although Pa AA9E and Pa AA9H are efficient cellulolytic AA9s, it appears clearly that observing a high activity on somehow simple cellulosic substrates (such as PASC or Avicel) cannot be taken as a token of efficiency once mixed with cellulases on more complex biomass.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that protein adsorption on solid substrates is a dynamic process that involves continuous structural changes in proteins as they reversibly adsorb and desorb. However, as the process progresses, numerous rearrangements between the two states may compromise the protein's structural integrity, resulting in irreversible structural alterations and protein activity loss [47,48]. For most of the enzymes, the highest fluorescence intensity was localized on the inner part of the cell wall, corresponding to secondary cell wall layers (SCW) S3 and S2 sublayers.…”
Section: Enzyme Adsorption On Native Poplar Cell Wallsmentioning
confidence: 99%